Protective effect of Lyophyllum ulmarium fibrolytic enzyme on liver injury induced in hyperlipidemia rats - LI Yu; SU Xin; ZHANG Jun-hui; ZHANG Rui-meng; SHEN Ming-hua (Shipin yu jixie, 2023)
Objective: To investigate the protective effect and mechanism of Lyophyllum ulmarium fibrinolytic enzyme （LUFE） on rats with hyperlipidemia. Methods: Hyperlipidemia models were established by feeding with a high-fat diet, and the model rats were gavaged with different doses of LUFE. HE stain was used to analyze the morphological changes of liver.The biochemical indexes of rat plasma were detected by colorimetric method.WB analyses the expression level of related proteins. Results: LUFE could alleviate the liver tissue injury of hyperlipidemia rats and reduce the plasma lipid level and IL-6, TNF-α，MCP-1，ALT，AST. LUFE can down regulate TLR4，MyD88，phosphorylated PI3K，phosphorylated Akt and phosphorylated NF-кB protein level. Conclusion: LUFE protects against hyperlipidemia-induced liver injury in rats by regulating PI3K/Akt/NF-кB and TLR4/MyD88/NF-кB signaling pathways.